Inpatient and home-based rehabilitation regimen after COVID-19 illness - Ramakant Yadav; Neha Dubey; Sunil Kumar; Vaibhav Kanti; Raj Kumar (Wolters Kluwer Medknow Publications, 2020)
The severe acute respiratory coronavirus-2 syndrome infection has spread worldwide and has an abrupt effect on human, economic, and health system. The data are collected from various relevant sources such as PubMed, Infection Prevention Control, World Health Organization novel coronavirus disease (COVID-19) situation update report, Australian and New Zealand Intensive Care Society guidelines, Society of Critical Care Medicine, World Confederation for Physical therapy guidelines, and from other Internet sources. It is observed that about 30% of COVID-19 patients with sepsis needed hospital rehabilitation, while 20% requires a home-based rehabilitation program. Based on the evidence, it is anticipated that severe and critical COVID-19 patients develop postintensive care syndrome, resulting in pulmonary disabilities, dyspnea on exertion, physical deconditioning, cognitive impairment, and mental health disturbances. Most of these symptoms may also occur in patients recovered from symptoms, or who were not admitted to intensive care unit, or in older adults with chronic health conditions, or who have been deconditioned due to mobility disability, social isolation, etc. Such patients need access to effective pulmonary therapy, functional rehabilitation, and stress management in the hospital- and home-based settings to regain their previous independence level. The evidence suggests that viruses could even survive in the oropharyngeal cavity and stool for up to 15 days after COVID-19 infection has been declared cured. The physiotherapist must take proper safety measures before managing patients at home; a virtual care therapy is therefore highly recommended. Due to the increasing demands of hospital beds, the patients may need to be discharged earlier than expected. Rehabilitation act as adjuvant therapy in preparing patients for discharges, reducing the experience of disability, and ensuring the quality of treatment among recovered/discharged COVID-19 patients in hospital- or home-based settings.